2013
DOI: 10.3982/te1135
|View full text |Cite
|
Sign up to set email alerts
|

Effective affirmative action in school choice

Abstract: The prevalent affirmative action policy in school choice limits the number of admitted majority students to give minority students higher chances to attend their desired schools. There have been numerous efforts to reconcile affirmative action policies with celebrated matching mechanisms such as the deferred acceptance and top trading cycles algorithms. Nevertheless, it is theoretically shown that under these algorithms, the policy based on majority quotas may be detrimental to minorities. Using simulations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(52 citation statements)
references
References 40 publications
(53 reference statements)
1
50
0
1
Order By: Relevance
“…The first feature alone is not novel and it has been extensively utilized in the context of school choice with affirmative action. Examples of such applications include controlled choice models of Abdulkadiroglu and Sönmez (2003) with majority quotas and Hafalir, Yenmez, and Yildirim (2011) with minority reserves, 29 as well as the school choice model of Westkamp (2011) with complex constraints. However, in contrast to cadet-branch matching, object priorities satisfy the substitutes condition in all of these earlier applications.…”
Section: Matching With Slot-specific Prioritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The first feature alone is not novel and it has been extensively utilized in the context of school choice with affirmative action. Examples of such applications include controlled choice models of Abdulkadiroglu and Sönmez (2003) with majority quotas and Hafalir, Yenmez, and Yildirim (2011) with minority reserves, 29 as well as the school choice model of Westkamp (2011) with complex constraints. However, in contrast to cadet-branch matching, object priorities satisfy the substitutes condition in all of these earlier applications.…”
Section: Matching With Slot-specific Prioritiesmentioning
confidence: 99%
“…30 28 Biró, Fleiner, Irving, and Manlove (2010) reported that college admissions in Hungary have a similar feature, where part of the slots at each department are state-financed while the rest are privately financed. 29 Hafalir, Yenmez, and Yildirim (2011) considered a school choice model where minority students are favored at a fraction of slots at each school. Rather than fully blocking the access of majority students, they advocated favorable treatment of minority students for these slots through increased priority.…”
Section: Matching With Slot-specific Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we develop a general framework for handling these sorts of slot-specific priority structures. 3 Our model embeds classical priority matching settings (e.g., Balinski andSönmez 1999, Abdulkadiroglu andSönmez 2003), models of affirmative action (e.g., Kojima 2012, Hafalir et al 2013, and the cadetbranch matching framework (Sönmez andSwitzer 2013, Sönmez 2013), as well as a new market design problem we introduce: airline seat upgrade allocation. 4,5 We show how markets with slot-specific priorities can be cleared by the cumulative offer mechanism, which generalizes agent-proposing deferred acceptance Milgrom 2005, Hatfield andKojima 2010).…”
Section: Introductionmentioning
confidence: 99%
“…saving nearly 230-300 additional liver patients in South Korea alone (see the last line of Table IV in Section 3.2 and Table VI in Appendix B.2. Increasingly, economists are taking advantage of advances in technology to design new or improved allocation mechanisms in applications as diverse as entry-level labor markets (Roth and Peranson (1999)), spectrum auctions (Milgrom (2000)), internet auctions (Edelman, Ostrovsky, and Schwarz (2007), Varian (2007)), school choice (Abdulkadiroglu and Sönmez (2003)), kidney exchange (Roth, Sönmez, and Ünver (2004, 2007), course allocation (Sönmez and Ünver (2010), Budish and Cantillon (2012)), affirmative action (Kojima (2012), Hafalir, Yenmez, and Yildirim (2013), Echenique and Yenmez (2015)), cadet-branch matching (Sönmez and Switzer (2013), Sönmez (2013)), refugee matching (Moraga and Rapoport (2014), Jones and Teytelboym (2016)), and assignment of arrival slots (Schummer and Vohra (2013), Schummer and Abizada (2017)). Our paper contributes to the emerging field of market design by introducing a new application in dual-donor organ exchange, and also to transplantation literature by introducing three novel transplantation modalities.…”
Section: Introductionmentioning
confidence: 99%